Electronic module assembly. Issue 2 (2021) - Franke, Jörg; Wang, Lihui; Bock, Karlheinz; Wilde, Jürgen
Abstract: Electronics is the vital basis for innovations and the essential enabler for global trends like connectivity, electro mobility and renewable energies. These applications require high performance and reliability of the electronic modules. Their assembly combines very heterogeneous process chains like remarkable productive and diminutive surface mount technology (SMT), powerful and robust power electronic interconnection techniques, as well as pioneering reel-to-reel based organic electronic printing. After briefly outlining the enormous global economic impact of electronic modules, this paper presents the state of the art of electronic module assembly including substrate materials, electronic components, packaging and assembly processes as well as quality and reliability testing methods.